The Use of Poster Presentation as a Speaking Technique in Health-Issue Based Instruction: A Study of Public Health Students - Ahsan Muzri.S; Muzdalifah Mahmud; La Sunra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigated the use of poster presentation in health-issue-based speaking instruction and examined its effect on the speaking ability of Public Health students. The study employed a pre-experimental one-group pretest-posttest design involving 22 beginner-level Public Health students at Universitas Pancasakti Makassar, Indonesia. The treatment was conducted over eight meetings, with each meeting lasting 2 × 45 minutes, and focused on the topic of healthy and unhealthy food. Students prepared and orally presented posters as part of the instructional activities. Speaking performance was assessed by two raters using an analytic rubric adapted from Brown (2004), covering fluency, pronunciation, grammar, vocabulary, and comprehensibility. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, a paired sample t-test, and Cohen’s d. The findings showed that the students’ mean speaking score increased from 60.83 in the pre-test to 64.06 in the post-test, with a mean difference of 3.23. The paired sample t-test revealed a statistically significant difference between the two scores (t = 4.163, df = 21, p < .001). The effect size analysis yielded Cohen’s d = 0.89, indicating a relatively strong within-group effect, although the raw-score improvement remained modest. These findings suggest that poster presentation can serve as an effective instructional strategy for improving speaking performance by helping students organize ideas, prepare content, and communicate information more clearly. The study also shows that integrating health-related topics into speaking instruction can make learning more contextual, meaningful, and relevant to Public Health students’ academic and professional needs.